Utility of Saline-Induced Resting Full-Cycle Ratio Compared with Resting Full-Cycle Ratio and Fractional Flow Reserve - Takao Sato; Sonoka Goto; Yusuke Ohta; Yuji Taya; Sho Yuasa; Minoru Takahashi; Masaaki Okabe; Yoshifusa Aizawa (Journal of Interventional Cardiology, 2020)
Background. The saline-induced distal coronary pressure/aortic pressure ratio predicted fractional flow reserve (FFR). The resting full-cycle ratio (RFR) represents the maximal relative pressure difference in a cardiac cycle. Therefore, the present study aimed to compare the results of saline-induced RFR (sRFR) with FFR. Methods. Seventy consecutive lesions with only moderate stenosis were included. The FFR, RFR, and sRFR values were compared. The sRFR was assessed using an intracoronary bolus infusion of saline (2  mL/s) for five heartbeats. The FFR was obtained after an intravenous injection of papaverine. Results. Overall, the FFR, sRFR, and RFR values were 0.78 ± 0.12, 0.79 ± 0.13, and 0.83 ± 0.14, respectively. With regard to anatomical morphology were 40, 18, and 12 cases of focal, diffuse, and tandem lesion. There was a significant correlation between the sRFR and FFR (R = 0.96, p<0.01). There were also significant correlations between the sRFR and FFR in the left coronary and right coronary artery (R = 0.95, p<0.01 and R = 0.98, p<0.01). Furthermore, significant correlations between sRFR and FFR were observed in not only focal but also in nonfocal lesion including tandem and diffuse lesions (R = 0.93, p<0.01 and R = 0.97, p<0.01). A close agreement on FFR and sRFR was shown using the Bland–Altman analysis (95% CI of agreement: −0.08–0.07). In the receiver operating characteristic curve analysis, the cutoff value of sRFR to predict an FFR of 0.80 was 0.81 (area under curve, 0.97; sensitivity 90.6%; and specificity 98.2%). Conclusion. The sRFR can accurately and safely predict the FFR and might be effective for diagnosing ischemia.